Uma nova proposta de antena planar multibanda para comunicações móveis - D'assunção Júnior, Adalido Gomes (2007)
The great interest observed in wireless communication systems has required the development of new configurations of microstrip antennas, because they are easily built and integrated to other microwave circuit components, which is suitable for the construction and development of planar antenna arrays and microwave integrated circuits. This work presents a new configuration of tapered microstrip antenna, which is obtained by impressing U-slots on the conducting patch combined with a transmission line matching circuit that uses an inset length. It is shown that the use of U-slots in the microstrip antenna conducting patch excites new resonating modes, that gives a multiband characteristic for the slotted microstrip antenna, that is suitable for applications in communication systems that operates several frequencies simultaneously. Up to this date, the works reported in the literature deals with the use of Uslotted microstrip rectangular antennas fed by a coaxial probe. The properties of a linear array of microstrip patch tapered antennas are also investigated. The main parameters of the U slotted tapered microstrip antennas are investigated for different sizes and locations of the slots impressed on the conducting patch. The analysis of the proposed antenna is performed by using the resonant cavity and equivalent transmission line methods, in combination with a parametric study, that is conducted by the use of the Ansoft Designer, a commercial computer aided microwave software well known by its accuracy and efficiency. The mentioned methods are used to evaluate the effect in the antennas parameters, like resonant frequency and return loss, produced by variations of the antenna structural parameters, accomplished separately or simultaneously. An experimental investigation is also developed, that consists of the design, construction and measurement of several U slotted microstrip antenna prototypes. Finally, theoretical and simulated results are presented that are in agreement with the measured ones. These results are related to the resonating modes identification and to the determination of the main characteristics of the investigated antennas, such as resonant frequency, return loss, and radiation pattern